Perancangan Aplikasi Quiz Menggunakan Metode Pengacakan Linear Congruential Generator (LCG) Berbasis Android - Riki Wahyudi; Hendra Handoko Syahputra Pasaribu (RJOCS (Riau Journal of Computer Science), 2015)
A quiz application that has element of Mobile Learning (M-Learning) in the Smartphone can certainly provide an attractive entertainment to the users, and can provide instructional media to add knowledge. Quiz is a form of game or mind in which the players (as individuals or in teams) attempt toanswer questions correctly to achieve the goal in learning. In this application, the users will be asked some questions about general knowledge, so the users are forced to think in answering the questions.The method used in the design of this application is the Linear Congruential Generator (LCG) method and the String Matching (SM) method, in which the LCG method functions to randomize question on the application, while the SM method functions to match the selected answer "true and false".